Transliterasi Aksara Arab dalam Pentalogan - Rizal Saiful Haq (Buletin Al-Turas, 2005)
The Principle of Arab-Latin transliteration is based on the system that used by scholars from  English-speaking countries, and accepted officially by American Library Association, Canadian Library Association and The LIbrary of Congres.